Irenaeus of Lyons - Grant, Robert M. (Robert McQueen), 1917-2014 (Routledge, 1997)
During the second century the Christian world was shaken by the Gnostics. Irenaeus came from Asia Minor via Rome to become bishop of Lyons, clarify Christian doctrines and fight the Gnostics with a major, five-volume work. He was a living part of his contemporary culture and his approach filled early Christian thought with new life. The writings of Irenaeus exist as a whole only in Latin and Armenian. This study offers translations of significant parts of his work, critically based on a complete reconstruction of the original Greek in the French series "Souorces Chretiennes" . It should be of use to students of the early church, both as an introduction to Irenaeus' thought, and as a collection of sources
Keywords: Irenaeus, -- Saint, Bishop of Lyon.; Irénée, -- saint, -- environ 130-environ 202.; Irenaeus, -- Saint, Bishop of Lyon; Irenaeus Lugdunensis, -- 2e E.; Irénée -- (saint; -- 013?-019?); Irenaeus (Lugdunensis); Christian saints -- France -- Biography.; Saints chrétiens -- France -- Biographies.; 11.51 early Christianity.; RELIGION -- Christian Church -- History.; BIOGRAPHY & AUTOBIOGRAPHY -- Religious.; RELIGION -- Christianity -- History.; Christian saints; France; Gnosticisme.; Teologi -- Teologi.; Electronic books.; Biographies; Biographies.